ANALISIS RESIKO BENCANA GEMPA BUMI UNTUK PENATAAN RUANG KABUPATEN BURU SELATAN - Prasetya, Hermawan (BPPT)
Law Number 26/2007 about Spatial Planning has been dedicating a spatial plan sound disaster mitigation. South Buru District, which as splitting district from Buru District, currently preparing spatial plan. This paper intends to conduct a risk analysis of the earthquake disaster that will be used to evaluate the concept of spatial plan of South Buru District. Risk analysis concist of set of analysis such as prone, vulnerability and risk analysis to earthquake disasters. Based on these analysis, indicates the level of risk to earth quake in the majority of South Buru area is low. Comparison between the risk map with the concept of spatial plan indicates that the placement locations of major activities in spatial concepts have been in accordance with the risk of earthquake.Keyword : earthquake, prone to disaster, vulnerability, risk analysis, spatial planning